In vitro screening of rice genotypes using polyethylene glycol under drought stress - Akte, J; Yasmin, S; Bhuiyan, MJH; Khatun, F; Roy, J; Goswami, K (Progressive Agriculture, 2016)
Five rice varieties viz. Binadhan-4, Binadhan-5, Binadhan-6, Binadhan-10 and Iratom-24 were evaluated in vitro under different water stress conditions. Several parameters such as germination percentage, shoot length, root length, shoot-root ratio, fresh weight, dry weight, turgid weight, relative water content and proline accumulation were studied. Drought condition was created by MS medium supplemented with five treatments of PEG, with a control such as 0%, 1%, 2%, 3% and 4% of PEG. The highest germination (100%) was found in the variety Binadhan-10 under low water stress conditions induced by 1% PEG. Similarly, the highest percentage of germination was found in all varieties under control condition (0% PEG). The lowest percentage of germination was obtained in the variety Iratom-24. But under severe stress (4% PEG), the highest percentage of germination was found only in the variety Binadhan-10. Moreover, the variety Binadhan-10 was found to be the best at 4% PEG for shoot length, root length, shoot-root ratio, relative water content and also the best at 1% PEG for fresh weight, dry weight, turgid weight. Water stress decreased relative water content and increased proline accumulation in rice. The highest relative water content was recorded in the variety Binadhan-10 and the lowest value recorded in the variety Binadhan-5. The highest proline content was obtained from the binadhan-6 at the highest treatment (4% PEG). Binadhan-10 showed the best performance almost in all the parameters under drought stress because of its own nature of tolerancy. Progressive Agriculture 27 (2): 128-135, 2016